In vitro activity of eight antifungal drugs against Chaetomiaceae. (13th November 2021) - Dolatabadi, Somayeh; Najafzadeh, Mohammad Javad; Houbraken, Jos; Vicente, Vania; de Hoog, Sybren; Meis, Jacques F
Abstract: The incidence of infections caused by uncommon Chaetomiaceae ( Chaetomium and related species) in humans has increased in the recent years. The in vitro activity of eight antifungal drugs (amphotericin B, five azoles, two echinocandins) against 42 morphologically identified Chaetomium strains was determined according to the Clinical and Laboratory Standards Institute (CLSI) guideline. The strains were subsequently identified based on sequences of the internal transcribed spacer 1 and 2 including the intervening 5.8S nrDNA region (ITS) and the partial β tubulin gene ( tub2 ). Chaetomium globosum (n = 24), was the most frequently isolated species, followed by Amesia atrobrunnea (syn. Chaetomium atrobrunnea, n = 6), Dichotomopilus dolichotrichus (syn. Chaetomium dolichotrichum, n = 2) and Acrophialophora jodhpurensis, Chaetomium coarctatum, C. elatum, C. gracile, C. subaffine, C. tarraconense, C. unguicola, Dichotomopilus sp ., Dichotomopilus variostiolatus, Ovatospora brasiliensis (all represented by a single strain). The geometric means of the minimum inhibitory concentrations/minimum effective concentrations (MICs/MECs) of the antifungals across all strains were (in increasing order): micafungin 0.12 µg/ml, itraconazole and posaconazole 0.21 µg/ml, amphotericin B 0.25 µg/ml, voriconazole 0.45 µg/ml, isavuconazole 0.54 µg/ml, caspofungin 2.57 µg/ml, and fluconazole 45.25 µg/ml. Micafungin had the lowest geometric mean followed by amphotericin B which had the largest range against tested isolates. All examined C. globosum strains had similar antifungal susceptibility patterns. Fluconazole and caspofungin could not be considered as an option for treatment of infections caused by Chaetomium and chaetomium-like species. Lay summary: Infections caused by uncommon fungi such as Chaetomium have increased in the recent years. Chaetomium globosum has been reported from onychomycosis and phaeohyphomycosis. This species often induces superficial infections in immunocompetent patients. The taxonomy of Chaetomium spp. has changed dramatically in the last years. Antifungal treatment is a crucial step for managing these kinds of infections. Therefore, the in vitro activity of eight antifungal drugs against Chaetomium strains was determined and β-tubulin ( tub 2) sequencing was applied to identify the strains. Chaetomium globosum was the most frequent species in our dataset. Based on the results of susceptibility testing, micafungin had the lowest geometric mean followed by amphotericin B. Fluconazole and caspofungin cannot be considered a proper treatment option for infections caused by Chaetomium and chaetomium-like species.